Pengaruh Biaya Promosi Dan Biaya Produksi Terhadap Volume Penjualan Al-Galla Industries Periode Januari 2019- Desember 2021 - Adi Maulana; Ari Arisman; Depy Muhamad Pauzy (Ebisnis Manajemen, 2023)
This study aims to determine the effect simultaneously and partially the effect of promotional costs and production costs on AL-Galla Industries Sales Volume for the period January 2019- Desember 2021 Tasikmalaya. The research method used in this research is quantitative analysis method with a case study approach. Data collected in the form of secondary and primary data. The data analysis in this study used Multiple Regression Analysis using SPSS version 25 software. The results showed that Promotion Costs and Production Costs had a simultaneous influence on AL-Galla Industries Sales Volume. Promotion costs have a partial effect on AL-Galla Industries. Production costs partially AL-Galla Industries Sales Volume